The Relationship Between Mental Health Literacy and Attitudes Towards Seeking Professional Mental Health Help Among Students - Amalia, Reza Fajar; Ekowati, Wahyu; Mulyaningrat, Wahyudi; Swasti, Keksi Girindra (Green Publisher Indonesia, 2025)
The likelihood of addiction increases as more school-aged youngsters use smartphones. When faced with an uncomfortable circumstance or pressure, kids with poor self-efficacy frequently turn to their smartphones as a coping strategy to instill a sense of security. This study aimed to understand the relationship between mental health literacy and students' attitudes towards seeking professional psychological help. The sampling technique used was stratified random sampling of 386 college students to fill out a questionnaire that assessed their mental health literacy and attitude towards seeking professional psychological help. The mean of mental health literacy score was 118 (SD=14.01) while the overall mean attitude towards seeking professional psychological help was 21 (SD=7.30). A correlation coefficient of r is found in statistical tests examining the relationship between the two variables. A significant correlation between the two variables is revealed by statistical testing (r=0.784, p=0.010). This study shows a significant correlation between mental health literacy and attitude towards seeking professional psychological help. Formulating strategies for education and promoting mental health services in higher education units is important.